Genetic variability, heritability and genetic advance in muskmelon (Cucumis melo L.) - Bhimappa, B.B.; Choudhary, H (Annals of Agricultural Research, 2017)
Highly significant differences were observed among 67 diverse muskmelon genotypes from differentvarietal groups studied for yield and yield contributing characters. Average fruit weight showedthe highest phenotypic and genotypic coefficient of variation closely followed by yield per plant.The lowest value was recorded for number of fruits per plant followed by number of primarybranches, days to first pistillate flower opening and days to first fruit harvest. All the charactersexhibited less difference between GCV and PCV values and traits like days to first pistillate floweropening, fruit length, node number of first fruit set showed nearly equal GCV and PCV valuesindicating least influence of environment on their expression. The heritability estimates weregenerally high (above 80%) for all the characters except number of fruits per plant (47.02%). Themaximum heritability was observed for seed length closely followed by fruit length. Genetic advanceas percentage of mean was highest for average fruit weight (kg) followed by fruit length (cm) andyield per plant (kg). High heritability coupled with high GAM was observed for fruit length (97.69,83.30%); heritability coupled with high to moderate genetic advance was observed for fruit lengthand days from pollination to fruit harvest indicating that they are governed by additive genes andcould be effectively improved through selection.